Reproductive Performance of Peanut Goats in Abeli, Nambo and Poasia Districts, Kendari City - Sudianto, Kadek Rai; Asminaya, Nur Santy; Aku, Achmad Selamet (Pascasarjana Universitas Halu Oleo, 2024)
This research aims to evaluate the performance of the breeding and reproductive aspects of peanut goats in Kendari City. This research was carried out in three Districts (Abeli, Nambo and Poasia) in Kendari city. Determining the research location was carried out using purposive sampling, namely by direct selection based on the criteria of the largest population of Peanut goats in Kendari city, Southeast Sulawesi. This research used the quantitative descriptive method to description data collection and results. The research variables observed were Age at first oestrus, Age at first calving, Re-mating time periode, calving interval (CI), mortality, Litter size, Kidding interval (KI). Research result showed that the goat mating technique used by breeders is natural mating. Methods for selecting livestock vary from not selecting them at all, selecting by considering the health of the livestock and selecting based on the livestock's body posture. The reproductive performance of local goats includes age at first heat, age at first birth, mating distance after calving, CI, KI, litter size, mortality and kid crop, respectively, 7.5 – 8 months; 12-18 months; 2 – 2.33 months; 7.5 – 8 months; 8 months; 1.33 – 2 tails; 2% and 200.00 – 225.00%.